Exploring a group of Limpopo Province's senior phase mathematics teacher's pedagogical content knowledge of algebra using content representations - Bopape, Mamogobo Eunicca (My University, 2016)
This research explored the pedagogical content knowledge (PCK) of algebra as held by a group of senior phase teachers in Limpopo Province, South Africa. Sixty-one teachers from different districts in the province participated in this study. This qualitative study used a case study design. Data was collected using a test and content representation (CoRe) matrix. The results were analysed through analysis of narratives. The study revealed that most of the teachers could not identify the main concepts that are taught in algebra. It was discovered that some could not differentiate between algebra and arithmetic. The findings also point out that the teachers had inadequate knowledge of algebra subject matter. The participants were able to identify some of the concepts that learners were supposed to do in the next grades. The findings revealed that most of the participants did not know the importance of teaching algebra. It was revealed that most participants could not identify the learners‘ difficulties; they could not specify the procedures they followed when teaching the identified main concepts in algebra, or give reasons for using those procedures. Furthermore, they could not specify factors that influenced their teaching. However, they were able to indicate different methods they used to assess learners‘ understanding. It was concluded that these teachers had inadequate PCK of senior phase algebra. The study recommends development programmes for both subject matter knowledge and PCK for practising teachers. Keywords: pedagogical content knowledge, content representations (CoRes), algebra, senior phase mathematics teachers.
Thesis (M.Ed. (Mathematics)) ---University of Limpopo, 2016
Keywords: Content representations (CoRes); Senior phase mathematics teachers; pedagogical content knowledge algebra; Mathematical constants; Mathematics linguistics; Mathematics teachers; Mathematics -- South Africa -- Limpopo